Climate services needs in Battambang province: Rice cultivation and cash crops (cassava and maize) - Barlis, Angelica; Vu Huong, Ngan; Swaans, Cornelis P.M.; Soksophors, Yim (2022)
This info brief presents the key findings from the climate risk workshop (CRW) in Cambodia specifically from the province of Battambang. CRW is part of the climate service demand assessment by determining the climate and risk impact on main agricultural livelihoods, mapping the current and available farm management practices that farmers and local networks carry out to cope with climate variability to identify opportunities for improved practices using climate information and agro-advisory services.